Investigating Cumin Uprooting Dynamics: The Roles of Taproot Properties and Soil Resistance - Sheng Tai; Zhong Tang; Bin Li; Shiguo Wang; Xiaohu Guo (Agriculture)
Cumin (Cuminum cyminum L. cv.′Xin Ziran 1′), classified within an agricultural crop, necessitates uprooting as a critical harvesting process. In this paper, we tried to study the force dynamics behind direct cumin uprooting by developing mechanical models for field uprooting and taproot–soil friction. A mechanical model for cumin uprooting and a friction model between the cumin taproot and sandy loam soil were built. The coefficient of static friction was determined using laboratory experiments. Pull-out, tensile force, and field uprooting experiments were conducted to validate the model. The physical and mechanical properties of the taproot were also measured. DEM simulation was employed for pull-out analysis. The static coefficient of friction between the cumin taproot and sandy loam soil was found to be approximately 0.766. The mechanical model showed high precision (0.4% and 5% error rates). Measured taproot properties included 80.91% moisture content, 0.40 Poisson’s ratio, 15.95 MPa elastic modulus, 5.70 MPa shear modulus, and 3.49 MPa bending strength. A DEM simulation revealed agreement with experimental observations for maximum frictional resistance at pull-out. The minimum resistance was noted at the extraction angle of 60°. The developed mechanical model for cumin uprooting was satisfactory in accuracy. Overcoming initial soil resistance is the primary factor affecting pull-out force magnitude. The optimized extraction angle had the potential to decrease uprooting resistance, improving harvesting efficiency.